2009
DOI: 10.1111/j.1440-1754.2008.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

The parent‐reported prevalence and management of peanut and nut allergy in school children in the Australian Capital Territory

Abstract: Among a highly representative sample of children at school entry, 1 in 30 parents reported their child to have a strong allergic reaction to nuts and over 1 in 50 are estimated to have diagnostic test-confirmed peanut sensitisation, based on parent report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
(54 reference statements)
3
10
0
Order By: Relevance
“…Although that includes children of all ages and because some outgrow nut allergy with age, higher prevalence in younger age groups such as in this study would be anticipated. However, our findings are consistent with other Australian population-based studies, including data from the Australian Capital Territory where parent-reported nut allergy prevalence amongst 5-year-old school entrants in 2009 was 3.8% (95% CI 3.2-4.4%) [17]. Likewise, the prevalence of parentreported peanut allergy amongst a cohort of 4000 Australian children aged 4-5 years sampled from across each of the statesand along the full latitude gradient of Australia, was found to be 2.9% [18].…”
Section: Discussionsupporting
confidence: 91%
“…Although that includes children of all ages and because some outgrow nut allergy with age, higher prevalence in younger age groups such as in this study would be anticipated. However, our findings are consistent with other Australian population-based studies, including data from the Australian Capital Territory where parent-reported nut allergy prevalence amongst 5-year-old school entrants in 2009 was 3.8% (95% CI 3.2-4.4%) [17]. Likewise, the prevalence of parentreported peanut allergy amongst a cohort of 4000 Australian children aged 4-5 years sampled from across each of the statesand along the full latitude gradient of Australia, was found to be 2.9% [18].…”
Section: Discussionsupporting
confidence: 91%
“…Our study results also confirmed our previous finding of a positive association between parental reported nut allergy and the child having a regular GP [25]. We speculate that children with an allergy are more likely to see a regular GP for diagnosis, follow-up, and prescription for adrenalin if the allergy is severe.…”
Section: Discussionsupporting
confidence: 91%
“…Of the remaining 10% of children who were reported not breast fed, parent-reported nut allergy prevalence was 2.72%—the likelihood of developing a reported nut allergy was 1.5 times higher in breast fed children than in nonbreast fed children. These findings are replicated in earlier studies which also concluded that nut allergy was more likely in children who had been breast fed [25]. …”
Section: Discussionsupporting
confidence: 82%
“…Food‐induced allergic reactions, and life‐threatening food‐related anaphylaxis, are major medical and public health concerns with children reported to be at highest risk . Australia has one of the highest rates of allergic disease in the world with 1 in 20 Australian children found to exhibit an immunological response to specific foods .…”
Section: Introductionmentioning
confidence: 99%